Implementation of Supreme Court Regulation No. 1 of 2016 on Mediation Procedure in Divorce Cases During the Covid-19 Pandemic at Religious Courts in Medan City - Kusmalina; Budi Hartono; Dumasari Harahap (PERSPEKTIF, 2023)
This study undertakes an analysis of the implementation of Supreme Court Regulation (Perma) No. 1 of 2016 concerning Mediation Procedure I in the settlement of divorce cases during the COVID-19 pandemic at Religious Courts in Medan City, while also identifying inhibiting factors. A descriptive qualitative research method is employed due to the nuanced nature of the issues at hand. Key informants (Vice Chairman of the Religious Courts in Medan City), main informants (mediators), and additional informants (court clerks) constitute the research subjects. Data collection methods encompass observation, interviews, and documentation. Data analysis includes data reduction, presentation, conclusion drawing, and verification, with data validity confirmed through triangulation. The implementation of Perma No. 1 of 2016 is evaluated through the lens of Edward III's theory, encompassing communication, disposition, resources, and bureaucratic structure. However, the appointment of mediator judges remains suboptimal. Mediation of divorce cases at the Religious Courts in Medan City is perceived as less effective, supported by the limited number of successfully mediated cases. Inhibiting factors include the scarcity of mediator judges, inadequate accessibility to mediation rooms for many individuals, and a lack of public awareness regarding the significance of mediation in case settlements.